INITIAL MANAGEMENT OF HYPOVOLEMIC SHOCK IN CHILDREN – A SYSTEMATIC REVIEW OF THE LITERATURE - Medeiros Paixão, Vitória; Lacerda Costa Marinho , Samira; Fernandes Mascarenhas , Ana Clara; Diniz Oliveira , Monalisa Diniz Oliveira; dos Santos Silva, Ingrid Evelyn; Ribeiro Pereira de Assis, Celiana Ribeiro Pereira de Assis (Revista de Patologia do Tocantins, 2025)
Introduction: Hypovolemic shock in children is a critical condition that occurs when there is a significant loss of intravascular volume, leading to decreased tissue perfusion and compromising organ function. It can be triggered by several factors, such as dehydration, hemorrhages and gastrointestinal conditions, which can lead to a rapid deterioration of the clinical condition. The patient presented with tachycardia, hypotension, weakness, and signs of hypoperfusion, requiring early evaluation and diagnosis. Initial treatment focuses on rapid rehydration and volume replacement, as well as specific measures to address the underlying cause. Thus, the present study aims to perform a systematic review of the literature on the initial management of hypovolemic shock in children. Methodology: This systematic literature review study was developed from the search of indexed articles, cross-sectional studies and retrospective case studies, in which 20 articles were found in the period from 2015 to 2024, consulted in the National Library of Medicine (PubMed MEDLINE) and Scientific Electronic Library Online (SciELO) databases. Of these 10, 3 articles were selected for the systematic review of the literature. Articles were included considering the type of shock, which is hypovolemic shock, the age group of children aged 0 to 10 years, and the publication date from 2015 to 2024. Results and discussion: It was observed that in most cases, there is a good response of the pediatric group to volume replacement with colloid fluids. However, if there is no response to fluids, which is assessed by improving vital signs, level of consciousness, and diuresis, it may be necessary to consider the use of vasoactive drugs. Conclusion: The initial management of hypovolemic shock in children is a critical intervention that can save lives. Early identification, appropriate support, and volume resuscitation are essential steps to restore perfusion and minimize complications. Continuous training of health teams in emergency protocols is critical to improving outcomes in children affected by this condition.